The Influence of Business Capital, Technology, and Labor On the Income of Food Industry MSMEs in Ponorogo Regency - Putri Fatmaningrum; Shinta Maharani; Asmak Ab Rahman (Niqosiya: Journal of Economics and Business Research, 2025)
Introduction: Ponorogo Regency is a region with diverse livelihoods. However, among these many livelihoods, there are 42,720 MSMEs. This study was conducted because there is a difference between theory and reality in the field, especially regarding the factors that influence MSME income. In general, large capital, utilization of technology, and the number of workers are considered to increase business income. However, observations show that not all MSMEs with large capital, adequate technology, and a large workforce generate high income. Therefore, this study aims to examine and analyze the effect of business capital, the role of technology, and labor on the income of MSMEs in the food industry sector in Ponorogo Regency. Research Methods: This study uses a quantitative approach with a questionnaire as the data collection method. The analysis technique used is multiple linear regression with the help of SPSS version 22. The sample in this study amounted to 100 randomly selected MSMEs. The results of the study indicate that partially and simultaneously, the variables of business capital, technology, and labor have a positive and significant effect on MSME income. Result: Based on the results of the determination coefficient analysis, these three variables have an influence of 61.1% on the income of MSMEs in the food industry sector in Ponorogo Regency, while the remaining 38.9% is influenced by other variables outside this study.